Multiply the first equation by -2:
x+4=-32
Subtract 4:
x=-36
For the second - multiply by -2/3:
-14=x-2
Add 2:
x=-12
2006-11-02 09:33:06
·
answer #1
·
answered by Pascal 7
·
0⤊
0⤋
1. - 1/2(x + 4) = 16
- 1/2x -2 = 16
- 1/2x - 2 +2 = 16 + 2
- 1/2x = 18
-1/2x / -1/2 = 18/ - 1/2
x = 18( -2/1)
x = - 36
2. 21 = -3/2(x - 2)
21 = -3/2x + 6/2
21 = - 3/2x + 3
21 - 3 = - 3/2x + 3 - 3
18 = - 3/2x
18/ -3/2 = -3/2x/-3/2
18(-2/3) = x
-36/3 =x
-12 = x
2006-11-02 10:53:59
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
1. First multiply each side by -2
x+4=-32
x=-36
2. First multiply by -2/3
-14=x-2
-12=x
2006-11-02 09:34:41
·
answer #3
·
answered by michmadman 1
·
0⤊
0⤋
I would first multiply by the LCD toget rid of the denominator, then go from there.
I did the 2cd one first
.Mult by 2
42=-3(x-2)
Divide by -3 since it goes into 42 evenly
-14=x-2
add 2
-12=x
1. mult by -2
x+4=-32
sub 4
x=-36
2006-11-02 09:36:19
·
answer #4
·
answered by mom 7
·
0⤊
0⤋
#1. -1/2x-2=16
-1/2x =18
x = -36
#2. -3/2x + 3 = 21
-3/2x = 18
x = - 12
hope this helps!
2006-11-02 09:33:32
·
answer #5
·
answered by KiKi E 2
·
0⤊
0⤋
-1/2 (x+4) = -0.5x - 2 = 16
-x - 4 = 32
-x = 36
x = -36
21 = -3/2 (x-2)
21 = -1.5x + 3
18 = -1.5x
-12 = x
2006-11-02 09:33:35
·
answer #6
·
answered by disposable_hero_too 6
·
0⤊
0⤋
Its basic algerbra. get rid of the fraction first by multpling both sides by the bottom and mutlipling both by the top. Then the () drop out and then its as easy as adding and subtracting.
1.x=-36
2.x=-12
2006-11-02 09:34:10
·
answer #7
·
answered by zspace101 5
·
0⤊
0⤋
-1/2(x+4)=16
-x/2-2=16
-x/2=18
-x=36
x=-36
and 21=-3/2(x-2)
21=-3x/2+3
18=-3x/2
36=-3x
-12=x
2006-11-02 09:34:48
·
answer #8
·
answered by cmadame 3
·
0⤊
0⤋
-1/2(x+4)=16
-o.5(x+4)=16
-0.5(x+4)/-0.5 =16/-0.5
x+4= -32
x+4-4= -32-4
x= -36
2006-11-02 09:43:00
·
answer #9
·
answered by rose 2
·
0⤊
0⤋